Influence of Reproductive Health Education on Adolescent Self-Efficacy - Herlianty; Evi Sridahrianti; Ni Ketut Sumidawati; Mira Kohmala Bauw (The Indonesian Institute of Science and Technology Research, 2026)
Adolescence is a transitional period marked by vulnerability to various reproductive health problems, including physical, mental, and social challenges. Limited knowledge about reproductive health often leads adolescents to engage in risky behaviors and exhibit low self-efficacy in maintaining their well-being. Self-efficacy refers to an individual’s belief in their ability to perform actions necessary to achieve desired outcomes. In reproductive health, it reflects adolescents’ confidence in making informed decisions and adopting protective behaviors. Health education is therefore a strategic intervention to improve adolescents’ knowledge, attitudes, and confidence regarding reproductive health. This study aimed to examine the effect of reproductive health education on adolescents’ self-efficacy in the working area of UPT Puskesmas Kota Enrekang Regency. A quasi-experimental design with a one-group pretest-posttest approach was employed. A total of 80 adolescents were selected using purposive sampling, and the intervention was delivered through leaflet-based health education. Self-efficacy was measured using a 20-item questionnaire. Before the intervention, only 13.7% of respondents demonstrated good self-efficacy, while 86.3% were categorized as low. After the intervention, there was a significant increase in the mean self-efficacy score from 38.56 to 72.12, with a mean difference of 33.56 and a p-value of 0.009. These findings indicate that reproductive health education significantly improves adolescents’ self-efficacy. The study highlights the importance of integrating structured reproductive health education into school and community programs to empower adolescents, reduce risky behaviors, and promote healthier future generations in Indonesia.